TOTAL BAKTERI ASAM LAKTAT (BAL) PADA KOMBUCHA CASCARA DALAM BERBAGAI KONSENTRASI PEMANIS STEVIA - Rihibiha, Dwi; Herawati, Eki; Rizqiyah, Naeli Sri (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2022)
Cascara is discarded outer skin of coffee which can be processed into various beverages, including kombucha. Bacteria in kombucha are predominantly Gluconacetibacter dan Lactobacillus, usually known as lactic acid bacteria. Concentration of sugar in fermentation plays important role for the growth of lactic acid bacteria. In this study, we used stevia sweetener in cascara kombucha fermentation. Stevia sweetener was added in various concentration: 2,5%, 5%, dan 7,5%. After 14 days of incubation, pH of kombucha cascara decreased in all treatment groups. This result indicated bacteria and yeast in kombucha starter has been able to utilize stevia during fermentation. Subsequently, kombucha cascara were cultured in a specific medium for lactid acid bacteria, de-Mann Rogoassa and Sharp (MRS). Results showed the highest lactic acid bacteria was found in kombucha cascara with 2,5% stevia, and the lowest was found in kombucha cascara with 7,5% stevia